2007
DOI: 10.1136/hrt.2006.094722
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of paclitaxel-eluting stents in saphenous vein grafts: clinical and angiographic follow-up results from a multicentre study

Abstract: Objective: To define the clinical and angiographic follow-up results after implantation of paclitaxel-eluting stents (PESs) in stenotic saphenous vein grafts (SVGs). Design: Prospective multicentre study. Comparison with a control group. Methods: 60 consecutive patients with 65 lesions located in 65 SVGs (mean (SD) age of vein grafts 11.3 (5.7) years) treated with PES (V-Flex Plus, 2.7 mg/mm 2 paclitaxel, Cook) and 60 patients with 60 SVG lesions treated with bare metal stent (BMS) were included. Lesions had t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 28 publications
2
30
0
1
Order By: Relevance
“…Zotarolimus-eluting stents were used in a minority of patients (8%) in 1 study. 26 Five studies used SES exclusively, 12,20,22,31,33 whereas only 3 studies 13,23,32 reported outcomes with PES for the DES group. When specified, treatment with aspirin was quite homogenous in the studies.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zotarolimus-eluting stents were used in a minority of patients (8%) in 1 study. 26 Five studies used SES exclusively, 12,20,22,31,33 whereas only 3 studies 13,23,32 reported outcomes with PES for the DES group. When specified, treatment with aspirin was quite homogenous in the studies.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…In the DELAYED RISCC study, 12 clopidogrel was administered for at least 2 months in all patients. Follow-up ranged from 6 months 23,25 to 48 months, 18 for a weighted average follow-up of 22.3 months.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in cohorts with intermediate and high risk, such as in the context of complex (35), (85), (86), (87), (88), (89) (90), (89), (90) (35), (41), (87), (92), (93) (48), (94), (95), (90), (96), (97) (48), (98), (99), (100), (101), (102), (97) (103), (104) …”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of DES in SVG remains uncertain due to contradictory data that supports lower rates of revascularization with DES [11][12][13][14][15][16][17][18][19]; clinical equivalence to BMS [20][21][22][23][24]; or even an excess of clinical events associated with the use of DES in SVG disease [25][26][27]. Indeed, the DELAYED RRISC trial showed increased mortality in patients treated with DES.…”
Section: Introductionmentioning
confidence: 99%